Evaluation of a water management training program in Tajikistan leads to redesign to target women farmers and informs Feed the Future Learning Agenda(WLE-IWMI) - CGIAR Research Program on Water, Land and Ecosystems (2018)
United States Agency for International Development(USAID) re-oriented an irrigation investment in Tajikistan to include women, based on results of a study by the CGIAR Research Program on Water, Land and Ecosystems (WLE) and partners. The study evaluated the effectiveness of a water management training program. While the training is indeed effective in improving crop and water management, women were excluded from training despite their growing role in water management, as men migrate away and out of farming.